An Overview of Systematic Reviews of Chinese Herbal Medicine for Alzheimer’s Disease - Liu, Nanyang; Zhang, Tingting; Sun, Jiahui; Yao, Jiuxiu; Ma, Lina; Fu, Jianhua; Li, Hao (Frontiers in Pharmacology, 2021)
Background: Multiple systematic reviews (SRs) have been conducted to evaluate the efficacy and safety of Chinese herbal medicine (CHM) in patients with Alzheimer's disease (AD). Here, we aim to perform an overview to assess the methodological quality and quality of evidence of the SRs to provide convincing data on the treatment of AD with CHM. Method: Six electronic databases including Chinese and English were searched, until April 31, 2021. Two researchers independently screen documents and extract data according to the predesigned rules. A Measure Tool to Assessment System Reviews 2 (AMSTAR-2) was used to investigate the methodological quality, and the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) was used to determine the quality of evidence for outcomes. Results: Twelve qualified SRs including 163 randomized controlled trials were reviewed. The methodological quality of the included SRs was considered extremely low assessed through AMSTAR-2. Compared with western medicines (WM) alone, CHM as an adjuvant treatment has shown significant effects in improving Mini-mental State Examination, Alzheimer’s Disease Assessment Scale-Cognitive, and Clinical Dementia Rating scores. The same is true for CHM alone. Regarding the effect on Activities Daily Living, neither the single CHM nor the combination with WM has an obvious effect. For the total effective rate, both single CHM and the combination with WM shown significant effects. Nine SRs suggested that CHM as adjuvant therapy or single-use had fewer adverse events than WM. Additionally, the quality of evidence for the main outcome was reviewed as low or extremely low according to GRADE profiler data. Conclusion: Current evidence suggests that CHM may be beneficial in improving the cognitive function of AD patients. However, we should be cautious about the evidence due to methodological flaws and low quality. High-quality RCTs are further needed to confirm the efficacy and safety of CHM for AD.